Improvement of soil geotechnical properties using pulverized fuel ash - Uwieng Anak, Gimos. (Universiti Malaysia Sarawak, UNIMAS, 2004)
The present study aimed at the use of locally available pulverized fuel ash (PFA) from Sejingkat P ower Corporation (SPC ), Kuching, Sarawak, to improve the geotechnical properties of soil. To achieve this, the soil samples were mixed with different percentages (i.e., 5, 10, 15 & 30%) of PFA contents. The amount of PFA added was on the basis of mass replacement (i.e., Soil - PFA mixture with 30% of PFA means, 70% of Soil and 30% of PFA). Standard Proctor test and California Bearing Ratio (CBR) test wer e conducted to determine the strength of the mixtures. The compaction results reveal that there is an increase in maximum dry density with the increase of PFA, while decreasing in optimum moisture content (OMC). The soaked CBR values for Soil - PFA mixtures were found to increase by 0.784 % and 0.12% with the increase of PFA content of 15% and 30%, respectively . The improvement of engineering properties of soil indicates that PFA can be used as a soil stabilizer and it would also provide an opportunity for the utilization of an industrial waste.